2015
DOI: 10.1111/acem.12565
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laboratory Testing on Emergency Department Length of Stay: A Multihospital Longitudinal Study Applying a Cross‐classified Random‐effect Modeling Approach

Abstract: Objectives: The objective was to examine the relationship between laboratory testing (including test volume and turnaround time [TAT]) and emergency department (ED) length of stay (LOS), using linked patient-level data from four hospitals across 4 years.Methods: This was a retrospective, multisite cohort study of patients presenting to any one of four EDs in New South Wales, Australia, during a 2-month period (August and September) in 2008, 2009, 2010, and 2011. Data from ED information systems were linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 25 publications
4
78
3
Order By: Relevance
“…for lab tests which has been shown to directly decrease ED length of stay (a 17-min increase in ED LOS per 30 min increase in lab TAT) [47]. Additionally, performing labs from triage could potentially identify patients requiring more immediate atention if there is a way to lag critical values to a responsible provider [48].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
“…for lab tests which has been shown to directly decrease ED length of stay (a 17-min increase in ED LOS per 30 min increase in lab TAT) [47]. Additionally, performing labs from triage could potentially identify patients requiring more immediate atention if there is a way to lag critical values to a responsible provider [48].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
“…abnormalities detected by coincidence, without clinical symptoms or suspicion) [2]. Notably, it was also shown that the median length of stay (LOS) in the emergency department (ED), even in a very developed setting, may increase by up to 10 min for every five additional tests ordered, and by up to 17 min for each 30-min increase in turnaround time [3].…”
Section: Introductionmentioning
confidence: 99%
“…2 Notably, it was also shown that the median length of stay (LOS) in the emergency department (ED), even in a very developed setting, may increase by up to 10 minutes for every five additional tests ordered, and by up to 17 minutes for each 30-minute increase in turnaround time. 3 Reliable evidence attests that urgent testing represents a large part of laboratory activity, with median percentage of stat analyses approximating 33% of all tests performed in clinical laboratories. 4 Additional evidence suggests that the panels of tests made available to the emergency physicians are extremely heterogeneous and variegated worldwide, so highlighting a rather poorly standardized scenario.…”
Section: Introductionmentioning
confidence: 99%